2008
DOI: 10.1530/rep-07-0505
|View full text |Cite
|
Sign up to set email alerts
|

Changes in LH secretion in response to an estradiol challenge in male- and female-oriented rams and in ewes

Abstract: Two experiments were conducted to determine whether an estradiol challenge could cause a female-type LH surge in castrated male-and female-oriented rams (MORs and FORs). Administration of 17b-estradiol to castrated MORs and FORs and ovariectomized ewes caused an initial reduction in LH secretion followed for 12-20 h by a surge release of LH in the ewes. No surge release of LH occurred in the MORs and FORs. The pattern of changes in LH secretion within rams and ewes did not differ between the breeding and nonbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
(42 reference statements)
0
9
0
1
Order By: Relevance
“…Male-oriented rams actively court other rams using male-typical sexual behaviors, while completely ignoring estrous ewes. Yet, with respect to their responses to gonadal hormones and capacity to exhibit sex-typical consummatory behaviors, male-oriented rams show male-typical mounting, not estrogen-induced receptivity and LH surge secretion (Stormshak et al, 2008). These observations can be interpreted to suggest that male-oriented rams, like female-oriented rams, are masculinized and defeminized with respect to mounting, receptivity, and gonadotropin secretion, but not for sexual partner preferences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Male-oriented rams actively court other rams using male-typical sexual behaviors, while completely ignoring estrous ewes. Yet, with respect to their responses to gonadal hormones and capacity to exhibit sex-typical consummatory behaviors, male-oriented rams show male-typical mounting, not estrogen-induced receptivity and LH surge secretion (Stormshak et al, 2008). These observations can be interpreted to suggest that male-oriented rams, like female-oriented rams, are masculinized and defeminized with respect to mounting, receptivity, and gonadotropin secretion, but not for sexual partner preferences.…”
Section: Discussionmentioning
confidence: 99%
“…This is because prenatal exposure to testosterone either from the fetal testis or exogenously administered, defeminizes the brain mechanisms controlling these responses (Foster et al, 2002). Tests show that the LH surge response is nonfunctional (defeminized) in male-oriented rams like it is in female-oriented rams (Perkins et al, 1995; Stormshak et al, 2008). Moreover, neither male- nor female-oriented rams express female-typical receptive behaviors in response to estradiol (Stormshak et al, 2008).…”
Section: Neither Male- or Female-oriented Rams Exhibit Lh Surge Respomentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this response could be an indicator of an incomplete brain masculinization. However, no rams secreted LH in response to estrogen treatments, regardless of their sexual preference (34,41) . Therefore in these studies it is suggested that brain masculinization in ruminants takes place in the prenatal period irrespective of sexual orientation, thus rendering impossible a LH response to estradiol treatments (2) .…”
Section: Diferencias En El Sistema Nervioso Centralmentioning
confidence: 95%
“…Por tanto, esta respuesta sería un indicador de una masculinización incompleta del cerebro. Sin embargo, ningún carnero secretó LH como respuesta a la administración de estrógenos, independientemente de que fueran homo o heterosexuales (34,41) . Por tanto, en estos trabajos se sugiere que el cerebro de los rumiantes, se masculiniza durante el periodo prenatal independientemente de la orientación sexual, imposibilitando la respuesta de LH al tratamiento con estradiol (2) .…”
Section: Endocrine Differencesunclassified